English language learning strategies employed by form four students in Sarawak / Felicia Genie Tersan - Tersan, Felicia Genie (2013)
This study was done to investigate the language learning strategies (LLS) employed by Form 4 students in Sarawak. LLS refer to particular behaviours or conducts, actions, steps or techniques students use to enhance their process of second language learning and improve their second language skills (Oxford, 1990). The study focused on three main aspects: the LLS used by the students, the LLS used by successful and less successful students as well as the variances in the choice of LLS used by the urban and rural students and how the strategies used by successful students can be adapted by rural students to improve their second language skills. A total of 200 students from two rural schools and two urban schools in Sarawak were selected from the best and weakest class to answer a questionnaire adapted from Oxford's (1990) Strategy Inventory of Language Learning (SILL). Students were asked to answer 40 questions and indicate their frequency of use of a given strategy on a four-point Likert scale (Always to Never). The researcher also interviewed students to further clarify their preferences. Descriptive statistics showed that the students were mostly moderate users of LLS. The most frequently used LLS was metacognitive strategies (M=2.86, SD=0.68) and the least frequently used LLS recorded was memory strategies (M=2.13, SD=0.49). Descriptive statistics also showed that the more 4 f. successful learners were more moderate users of LLS (M=2.68, SD=0.41) while the less successful learners were low strategy users (M=2.34, SD=0.48). Independent Samples T-test showed a significant difference in the use of four strategies by the urban students. Examples of the strategies were then proposed to the rural students and their responses were presented. Additionally, the findings of the study were reported and discussed. Finally, pedagogical implications were discussed recommendations on how to improve the study in future were suggested.